1993
DOI: 10.1021/ba-1993-0233.ch013
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Cross-Link Density and Rubber Additions on the Fracture Toughness of Polymers

Abstract: The effect of cross-link density on the efficacy of rubber toughening in thermosetting resins has been studied. Increasing the cross-link density changes the fracture toughness at a given temperature by both shifting the glass transition temperature (and thus the proximity of the test temperature to the glass transition temperature) and limiting the total crack-tip strain that can be realized at any given temperature.The temperature at which peak toughness is observed is shifted 50-120 °C lower in rubber-tough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…These results show that the effect which M c exerts on σ yT for the investigated material manifests itself distinctly trough a change in its T g . Similar findings were concluded in other epoxy systems by their investigators [4,5,13,17]. However, it can not be referred to the EPY compound with the values of M c ≥ 163 g/ mol because of too low postcuring temperature (T c ≤ 60 o C) of the material.…”
Section: Effect Of Temperature On Yield Behaviour In Compressionsupporting
confidence: 80%
“…These results show that the effect which M c exerts on σ yT for the investigated material manifests itself distinctly trough a change in its T g . Similar findings were concluded in other epoxy systems by their investigators [4,5,13,17]. However, it can not be referred to the EPY compound with the values of M c ≥ 163 g/ mol because of too low postcuring temperature (T c ≤ 60 o C) of the material.…”
Section: Effect Of Temperature On Yield Behaviour In Compressionsupporting
confidence: 80%
“…3 Nevertheless, the combination of the CET chemistry and the CSR toughening provides the DGE-BPA model epoxies with a much higher toughness and T g combination than the conventionally prepared DGEBA epoxy at low M c . 3,4,7,9 The fundamental reason(s) for such differences may be because of the uniformity of crosslinking in CET networks or the use of sulfanilamide curing agent. It is noted that when sulfanilamide is utilized to cure DGE-BPA epoxy, the crosslink density becomes high (M c ϭ 280 g/mole) and the T g becomes 200°C (Earls, J. D., personal communication, April 1997).…”
Section: Fracture Toughness Measurementmentioning
confidence: 99%
“…1 Since then, many endeavors have been made to gain an understanding on how the rubber particle size and type, 2,8,9 crosslink density of epoxy, 3,7,9 curing schedule, 4 and curing agents 4 influence the toughening effect of epoxies and other thermosets. While progress was made in the understanding of physics and mechanism(s) in rubber toughening, compromises brought about by the rubber toughening approach, such as reduction in modulus, thermal stability, dimensional stability, and processability, were found to be too big a compromise for many structural and electronic packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, while many studies have used CSR to successfully toughen epoxy resins, very few studies have explored highly cross-linked networks such as those based upon TGDDM. Indeed, Bradley et al showed that amongst three systems with Tgs between 189-225°C the core shell toughening response was absent [31]. Previous work on epoxy networks has indicated an inverse correlation between effective toughening and the bulk resin thickness relative to the crack front [26], [32], [33].…”
Section: Introductionmentioning
confidence: 99%